PENDEKATAN DEEP LEARNING UNTUK MENGATASI PHOBIA MATEMATIKA SEKOLAH DASAR - Maskur Huda; Azzahra Nadia Augustin; Annisa Rahmawati; Yulia Maftuhah Hidayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Math phobia arising from the assumption that math is abstract and difficult to understand becomes an obstacle for students, so a deep learning approach is needed to improve their learning experience and confidence. This study aims to analyze the role of deep learning approach as an effective solution to overcome math phobia in elementary school students. Based on 3 key aspects (mindful, meaningful, and joyful learning), deep learning encourages students' active involvement to create meaningful knowledge, build critical thinking capacity, and essentially overcome negative attitudes towards math early on. This research is qualitative research with phenomenological design. The methods used are observation, interview, and documentation. The results of this research activity show that the application of deep learning designed according to students' learning experiences can help reduce math phobia. Mindful, meaningful, and joyful learning creates a more positive learning atmosphere so that anxiety is reduced and learning outcomes are improved.